2014
DOI: 10.1387/ijdb.130340pd
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics of the human endometrium

Abstract: During the mid-secretory phase, the endometrium acquires the receptive phenotype, which corresponds to the only period throughout the endometrial cycle in which embryo implantation is viable. Endometrial receptivity is a crucial process and even more important in Assisted Reproductive Technologies (ART) where embryo-endometrial synchronization is coordinated through embryo transfer timing. Over the last decade, transcriptomic analyses performed on the human endometrium have shown that specific genomic signatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 100 publications
0
43
0
Order By: Relevance
“…Microarray-based expression profiling has technical limitations because it is limited by the nature of the probes included in the given platform as well as their sensitivity and specificity (Reis-Filho 2009;Díaz-Gimeno et al 2014). Nowadays, next generation sequencing (NGS) is an emerging technology that allows measurement of gene expression by RNA sequencing (RNA-seq).…”
Section: New Perspectives: Next-generation Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…Microarray-based expression profiling has technical limitations because it is limited by the nature of the probes included in the given platform as well as their sensitivity and specificity (Reis-Filho 2009;Díaz-Gimeno et al 2014). Nowadays, next generation sequencing (NGS) is an emerging technology that allows measurement of gene expression by RNA sequencing (RNA-seq).…”
Section: New Perspectives: Next-generation Sequencingmentioning
confidence: 99%
“…Nowadays, next generation sequencing (NGS) is an emerging technology that allows measurement of gene expression by RNA sequencing (RNA-seq). This new technology is capable of sequencing all the mRNAs present in a given sample, even the 25% of genes with low expression that remain undetected with standard microarray technologies (Mane et al 2009;Wang et al 2009;Díaz-Gimeno et al 2014).…”
Section: New Perspectives: Next-generation Sequencingmentioning
confidence: 99%
“…These original studies have been refined over the years using immunohistochemical (IHC) markers of cell proliferation, coupled with expression of cell cycle regulated proteins and steroid receptors that together with quantitative approaches in staged endometrial biopsies confirmed the Noyes staging and form the basis of current understanding [6]. Similarly, global gene expression studies of the whole human endometrium defined proliferative, early secretory, mid-secretory and late secretory endometrium into specific categories based on transcriptional and microRNA profiles, indicating the significance of the coordinated sequence of molecular events in response to sex steroids [710]. …”
Section: Introductionmentioning
confidence: 93%
“…During the WOI, the endometrium which has been primed by estrogen and progesterone is characterized by changes that are collectively termed endometrial receptivity (Lessey 2011). During the past decades, intensive morphological, histological, and molecular studies have defined the “signature” of the WOI in many species (Cheong et al 2013; Diaz-Gimeno et al 2014; Lessey 2011). …”
Section: Implantationmentioning
confidence: 99%